Software Pembelajaran Mandiri pada Latihan Stabilitas Berbasis Medicine Ball - Catur Supriyanto, (Kepelatihan Olahraga, 2011)
Stability Ball exercises in not only used for medical purpose but it is also used for the the athletes. These exercises are used to improve the stability, fitness and reduce fatiques. This research is a research and development research. It is conducted from April up to Juli 2009 at the Sport and Coaching Education Department in the Faculty of Physical Education and Sport Science UNESA Surabaya. This research develops the materials, the video tutorial software and then later tests the software.  The statistical result shows that the software significantly improves students understanding toward the stability ball exercises.